Global Pollinator Declines in the Anthropocene: Climate Change, Agriculture, and Food Security - Usama Shoukat; Muhammad Daud; Rifqa Afzal; Isma Gul; Muhammad Aqib; Sajjad Shafeeq; Adil, Muhammad (New Countryside, 2026)
Global pollinator populations are declining owing to climate shifts and agricultural expansion, threatening ecosystem stability, crop production, and food security. This review synthesizes empirical findings across diverse pollinator taxa, showing that increased temperature, altered precipitation, and extreme climatic events affect abundance, phenology, and distribution. Industrial farming intensifies these declines by fragmenting habitats and exposing pollinators to pesticides, thereby impairing the pollination of both wild plants and crops. Meta-analyses have revealed that reductions in pollinator diversity reduce the yield and nutritional quality of pollinator-dependent crops. A quantitative synthesis of 89 studies (1950–2023) highlights that climatic variability strongly impacts pollination processes in tropical regions, where reliance on wild pollinators and narrow thermal tolerances limit species’ adaptive capacity. This creates a “pollination-nutrition-health nexus” that links biodiversity loss to human dietary health. Despite the growing data from temperate regions, knowledge gaps persist in tropical ecosystems and non-bee pollinators. This review identifies five key priorities: (1) scaling standardized monitoring in underserved regions, (2) integrating ecological and socio-economic data, (3) employing trait- and network-based resilience metrics, (4) embedding pollinator conservation in climate policy, and (5) expanding technological and citizen-science approaches. We advocate a systems-oriented framework that unites biodiversity conservation, climate adaptation, and sustainable food systems. Protecting pollinators necessitates pollinator-friendly agriculture, habitat restoration, and the integration of pollination services into environmental management, recognizing pollinators as essential for planetary and human health.